ระบบบริการลูกค้าผ่านเว็บสำหรับการประปานครหลวง - สุริยันต์ วงศ์เมืองแก่น (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The objectives of this research are to design and develop the web-based customer service system for Metropolitan Waterworks Authority based on the data from current branch office database to inquire information according to user requirements. The system has been linked to main database system of Metropolitan Waterworks Authority separated in 2 sections. First, interactive web page for user interface using Java Server Page is connected directly to Oracle database server demonstrated by text and graph figure. Second, active store procedure is operated by database administrator.The researcher designed and developed the web-based customer service system for Metropolitan Waterworks Authority by design process, study and design the files and design the screens. The standard designed language for the system is UML (Unified Modeling Language). This language is used for structural design of system procedure and relationship of user interface. The system is based on Microsoft Windows operating system, Oracle database management, Apache Tomcat for web server and JAVA language for web application development. From system testing, the new system is able to increase more convenience and fast to Metropolitan Waterworks Authority customers. The customers are able to inquire their own water utilization information by just only accesses to the web page. They can verify both of historical and current information. The system is also useful for Metropolitan Waterworks Authority branch officer to be comprehensive service to customer. They can verify the variety of aggregated information quickly. Moreover, this system used as a prototype for other systems in the future.